Közönséges nád (Phragmites australis L.) levélfelület alakulása a kis-balatoni nádállományokban - Szanati, Angéla; Soós, Gábor; Anda, Angéla (GEORGIKON FOR AGRICULTURE, 2018)
Common reed is a macrophyte that can be found worldwide. It is widespread across Europe and Hungary in wet areas as well as weed in arable lands. Reed is the dominant species of reedy areas of still water, which - besides its ecological significance - also has water-cleaning action. During our examinations, we took measurements in a naturally reedy area situated in the Ingói-berek of Kis-Balaton Wetland, where the reed stand was composed of two sub-stands depending on water supplementation. We regularly took measurements of the following attributes: plant height, leaf area and calculated the leaf area index thereafter. The goal of our experiment was to detect differences in plant height and LAI values of the two reed stands with different water supplementations. To calculate the LAI it was necessery to perform stem counting on reed living in the water as well as on reed living on the bank.
Keywords: Kis-Balaton; common reed; LAI